EL PACÍFICO: UN PAISAJE MONUMENTAL PRECERÁMICO DEL FORMATIVO EN LA INTERCUENCA DE LOS RÍOS CHILLÓN Y RÍMAC - Flores Blanco, Luis A. (2017)
This paper is the first report that explores the problems of researching the first expressions of public architecture Archaic, on the central coast. And therefore, the potential it has to investigate a type of site as El Pacifico, located on a hill in the interbasin of the valleys of the Chillon and Rimac. And as I will demonstrated here, from the site you have a great viewshed, which also uses the topography to be as a powerful and meaningful place, arranged such to be seen and becoming a monumental landscape.